EXOGENOUS APPLICATION OF PROLINE ALLEVIATES SALT-INDUCED TOXICITY IN SAINFOIN SEEDLINGS - G.-Q. Wu1; R.-J. Feng; S.-J.Li; Y.-Y.Du (Journal of Animal and Plant Sciences, 2017)
To clarify the roles of exogenously applied proline in mitigating Na+ toxicity in sainfoin (Onobrychisviciaefolia Scop.), in this study, the changes of physiological and biochemical parameters were investigated in 15-day-old seedlings subjected with 0, 25 and 100 mmol/L NaCl with or without 2.5mmol/L proline for 7d. The results showed that both low salt (25mmol/L) and high salt (100mmol/L) significantly reduced fresh weight, dry weight, and water content (exception for low salt) in plants compared with the control. High salt also significantly increased concentration of malondialdehyde (MDA) and relative membrane permeability (RMP) in shoots. Our results showed that the addition of 2.5mmol/L proline remarkably mitigated Na+ toxicity in plants under both low- and high-salt stress. The mitigation of toxicity may be caused by regulating Na+/K+ ratio and increasing accumulation of proline. This study may provide physiological insights into understanding the mechanisms of salinity tolerance in plants treated with exogenous proline.
Keywords: legume forages; cell membrane stability; ions homeostasis; salinity tolerance; K+ uptake